Screening of avocado oil nanoformulations intended to skin delivery - Júlia Scherer Santos; Julia Cristina Koppe de Conto; Chana Medeiros da Silva; Rosana de Cassia de Souza Scheneider; Claudia Regina Müller (Facultad de Farmacia, Universidad de Granada, 2021)
Abstract Introduction: vegetable ingredients are increasingly common in skin products. Avocado oil is an ingredient of natural sources with various properties on the skin. In this work, crude avocado oil-loaded nanocapsules were evaluated regarding its physicochemical stability to obtain a formulation of skin delivery with adequate quality: suitable physicochemical stability, with low polydispersity and with a pH suitable for cutaneous application. Method: nanoparticle formulations with components variation were evaluated for 2 months. Nanoparticle formulation considered the most stable was further evaluated for 6 months. Furthermore, the oxidative stability of crude avocado oil loaded in nanocapsules and standard avocado oil was also performed to detect any sign of oil oxidation. Results: all formulations had negative zeta potential after 2 months of storage. pH values of nanoparticles remained stable throughout the test. Formulation with the lowest content of ingredients exhibited the highest stability after 2 months of storage. Nanoencapsulated avocado oil and crude avocado oil showed no evidence of oxidation. Conclusions: Aqueous dispersions with the lowest content of ingredients presented the best physicochemical stability. Therefore, we have demonstrated preliminary the feasibility of developing avocado-oil loaded nanocapsules.